Analisis Pengaruh Pengungkapan Environmental, Social, and Governance (ESG), Return on Assets (ROA), dan Enterprise Resource Planning (ERP) Terhadap Penghindaran Pajak - Lestari, Anis; Munandar, Agus (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure, Return on Assets (ROA), and Enterprise Resource Planning (ERP) on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample was selected using a purposive sampling technique, resulting in 112 observations. Multiple linear regression analysis was conducted using Stata 16 software. The empirical results indicate that ESG, ROA, and ERP simultaneously have no significant effect on tax avoidance. Partially, each independent variable also shows no significant influence. These findings suggest that ESG implementation and ERP adoption have not directly affected corporate tax behavior, while profitability is not a primary determinant of tax avoidance in the energy sector. This study contributes to the existing literature by incorporating ERP as a novel variable in tax avoidance research, providing additional insight into the role of integrated information systems in corporate taxation practices.